Predictive risk factors for facial nerve injury in temporomandibular joint replacement surgery. Issue 10 (December 2021) - Saeed, N.R.; McLeod, N.M.H.
Abstract: The objective of this study was to determine the prevalence of temporary and permanent facial nerve injury in total temporomandibular joint (TMJ) replacement surgery and to identify potential predictive risk factors. We made a retrospective review of case notes and opportunistic review of patients treated in a single tertiary referral unit by a single surgeon. For each patient a number of potential risk factors were determined, and the presence or absence of nerve injury recorded at 2 week follow up and a minimum of 12 months follow up. At 2-week review, facial nerve weakness was noted in 38/133 cases (28%) and at last follow up there were 4/133 cases (3%) with continuing (permanent) facial nerve weakness. Bilateral surgery, revision TMJ replacement, primary diagnosis, the number of previous surgeries and a history of recovered facial nerve injury all significantly increased the likelihood of temporary facial nerve injury, but not the likelihood of permanent facial nerve injury. Factors which increase the risk of temporary facial nerve injury are relatively predictable and include bilateral surgery, revision TMJ replacement, and multiple open TMJ surgeries. Risk factors associated with permanent injury are less predictable but are likely to be similar. The identification of such factors allows for the risk stratification of patients and improve informed consent. We also recommend that patients with a single, previously failed open TMJ surgery should be considered for early TMJ replacement and in multiply operated patients a subfascial plane of dissection is adopted.